2020
DOI: 10.3390/cancers12102934
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Data Augmentation with U-Net Segmentation Masks Improves Detection of Lymph Node Metastases in Breast Cancer Patients

Abstract: Deep learning models have potential to improve performance of automated computer-assisted diagnosis tools in digital histopathology and reduce subjectivity. The main objective of this study was to further improve diagnostic potential of convolutional neural networks (CNNs) in detection of lymph node metastasis in breast cancer patients by integrative augmentation of input images with multiple segmentation channels. For this retrospective study, we used the PatchCamelyon dataset, consisting of 327,680 histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In a study by Tschandl et al, both dermoscopic images and clinical close-ups were used to train the network; the combination was found to acquire a better result than the individual modalities [34]. Jin et al found that multiple extracted histological features, including nuclei, mitosis, epithelial, and tubular cells, could further improve the detection of lymph node metastasis in patients with breast cancer [35]. This study used a multichannel image input method to fuse multiple mode images in the VISIA system and discovered that it could improve the accuracy of our network to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tschandl et al, both dermoscopic images and clinical close-ups were used to train the network; the combination was found to acquire a better result than the individual modalities [34]. Jin et al found that multiple extracted histological features, including nuclei, mitosis, epithelial, and tubular cells, could further improve the detection of lymph node metastasis in patients with breast cancer [35]. This study used a multichannel image input method to fuse multiple mode images in the VISIA system and discovered that it could improve the accuracy of our network to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…A potential application in this direction could be prehistology GBPC-CT, where quantitative GBPC-CT data could be used for advanced tissue characterization leading to more precise and efficient sectioning in histology. Having the ability to access absolute quantitative GBPC-CT data could be used for deep learning and could also lead to improved histological diagnosis [184][185][186].…”
Section: Discussionmentioning
confidence: 99%
“…The authors adopted the CAM approach to identify patterns that influenced the model’s judgment on whether bacterial or viral pneumonia was present in the lungs. [ 34 ] used the IG technique to illustrate model attribution in the biomedical field of a breast cancer diagnosis. They claimed that models with more segmentation channels were better at focusing on specific parts of the image containing abnormal cells.…”
Section: Deep Learning Interpretability Techniques For Drmentioning
confidence: 99%